Chromate reductase activity in whole cells and crude cell free extract of Acinetohacter Haemolyticus - Abdul Karim, Norsuhada (2012)
Extensive use of hexavalent chromium, (Cr(VI)) in various industrial applications is a threat to human health, living resources and ecological system due to its high solubility, toxicity and carcinogenic effects. Previously, one locally isolated Cr(VI) reducing-resistant bacteria, Acinetobacter haemolyticus was used in the ChromeBac™ system, to remove toxic Cr(VI) from industrial wastewater. However, this process required long retention time which was primarily due to the toxicity of Cr(VI) towards immobilized whole cells used. The use of enzymes can be a suitable option for the effective Cr(VI) reduction as compared to whole cells. In view of this, this study was conducted to assess in vitro characterization of the enzymatic chromate reductase activity in cell free-extract (CFE) for maximum activity of Cr(VI) reduction. Cr(VI) resistance and reduction of A. haemolyticus was evaluated in Luria-Bertani (LB) medium supplemented with various Cr(VI) concentrations. From the results, A. haemolyticus can resist up to 200 mg/L Cr(VI) in LB broth compared to 100 mg/L Cr(VI) in LB agar. The FTIR and FESEM-EDX analysis suggested Cr deposition onto the bacterial cells surface via complex formation between Cr species and either carboxyl, hydroxyl or amide groups. TEM analysis showed that Cr(III) is also distributed in membrane and cytosolic fractions of bacteria. ESR analysis revealed that chromium accumulated on bacterial surface and mostly as Cr(III). The enzyme activity was optimal at 30°C and pH 7 in the presence of 1 mM Co2+. The Michaelis-Menten constants, Km and maximum reaction rate, Vmax obtained from the Lineweaver-Burke plot were 184.47 µM and 33.3 nmol/min/mg protein in the presence of 1 mM Co2+. Optimum Cr(VI) reduction by immobilized CFE-alginate was determined at initial pH 3, 100 rpm and 5 g wet weight beads dosage. Although immobilized enzyme system was able to reduce Cr(VI), the performance was not as good as the free enzyme. This study showed higher Cr(VI) reduction performance by free CFE compared to the use of whole cells demonstrate its potential for industrial application.